Conditions for a submanifold F^n from E^n + p to lie in E^2n − 1 - Nasedkina, Ya. S. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We consider a submanifold F^n with n principal directions in the space E^n + p, where p ≥ n_1.